Stable and Active Oxygen Reduction Catalysts with Reduced Noble Metal Loadings through Potential Triggered Support Passivation - Goehl, Daniel; Ruess, Holger; Schlicht, Stefanie; Vogel, Alexandra; Rohwerder, Michael; Mayrhofer, Karl J. J.; Bachmann, Julien; Roman-Leshkov, Yuriy; Schneider, Jochen M.; Ledendecker, Marc (ChemElectroChem, 2020)
The development of stable, cost-efficient and active materials is one of the main challenges in catalysis. The utilization of platinum in the electroreduction of oxygen is a salient example where the development of new material combinations has led to a drastic increase in specific activity compared to bare platinum. These material classes comprise nanostructured thin films, platinum alloys, shape-controlled nanostructures and core-shell architectures. Excessive platinum substitution, however, leads to structural and catalytic instabilities. Herein, we introduce a catalyst concept that comprises the use of an atomically thin platinum film deposited on a potential-triggered passivating support. The model catalyst exhibits an equal specific activity with higher atom utilization compared to bulk platinum. By using potential-triggered passivation of titanium carbide, irregularities in the Pt film heal out via the formation of insoluble oxide species at the solid/liquid interface. The adaptation of the described catalyst design to the nanoscale and to high-surface-area structures highlight the potential for stable, passivating catalyst systems for various electrocatalytic reactions such as the oxygen reduction reaction.
CRIS-Team WoS Importer:2020-04-21